Literasi Keuangan: Perencanaan Keuangan Modal Keberlanjutan Usaha Santri Tahfidz Laa Tahdzan Cinnangka Kota Depok Jawa Barat - Adi Supriadi; Sumaji, Ujang Syaifudin; Adriyanto, Muhammad Arif (Universitas Pamulang, 2025)
Community service activities by lecturers are included in the obligations. This is in accordance with the contents of the Tri Dharma, one of which is the task of carrying out community service. This task will be carried out routinely by lecturers throughout their careers in the academic world. Good working capital management not only keeps the business running smoothly, but also provides room for growth and development. With sufficient working capital, companies can take new opportunities, invest in innovation, and increase competitiveness in the market. So, make sure company working capital is always in a healthy condition, so that the business can continue to be sustainable and grow. The purpose of implementing this program is to provide motivation to the Santri Laa Tahdzan Cinangka, Depok City to better understand the importance of financial planning in business or enterprise. The methods used to be able to implement this work program are observation, coordinating with the students, providing counseling related to the importance of planning and the last is the reporting stage. The results of this service activity are guiding the students to be able to make good and effective financial plans. Keywords: Financial Planning, Capital and Business Sustainability